"Protect and Sustain" Certification of OCP. (2016) - Sadik, Ahmed
Abstract: As a leader in the Fertilizer and phosphate international market, OCP decided on April 2014 to get certification in compliance with the IFA's standard "Protect and Sustain". This standard is relating to product stewardship through the value chain of the phosphate: since the Research and Development to customer delivery. This certification consists on the compliance, of OCP management system and standards relating to security and SHE issues, with IFA's standards and criteria summarized in the 12 principles of IFA. The scope of this certification concerned Gantour-Safi integrated line from R&D to customer delivery, including mining operations, processing, chemical units, port facilities, external storage, supply chain, commercial and marketing, sourcing and contracting. The certification audit aims to check that Fertilizers and raw materials, additives and intermediate products are processed and manufactured, handled, stored, distributed and used in a safe way. To guaranty the success of this project in Five months, a task force was formed. This project team was motivated and exited to achieve this goal on time. The product stewardship performance of OCP was analyzed in September 2014 and OCP was awarded in IFA's summit in Marrakech on November 2014. This award with a high score (product steward excellence) was a result of our commitment to reach a high level in safety, security and sustainability.